Kolokacije v poslovni angleščini - Martič, Matjaž (Vestnik za tuje jezike, 2009)
The article starts with a brief theoretical overview that defines the term "collocation." It then presents a corpus study designed to determine the most frequent lexical collocations in Business English using the concordance program WordSmith Tools. This study is based on the assumption that English mainly consists of various (changeable) phraseological units and that both free combinations as well as completely "frozen" word combinations account for only a small share of the language. English is therefore a language of collocations and one can assume that this is valid not only for general English, but also for ESP and thus for Business English as well. In addition, the study investigated whether the most frequent collocations in this corpus could be found in major dictionaries of collocations, which would then establish their suitability for Business English purposes.
Keywords: angleščina; English; poslovni jezik; kolokacije; leksikalne kolokacije; besedne zveze; frazeologija; phraseology; kolokacijski slovarji; korpusna lingvistika; Corpus linguistics